Abundance and Diversity of Fruit Flies Species (Diptera: Tephritidae) in Bogor and Depok District - Octavia, Evy; Tarno, Hagus; Himawan, Toto; Setiawan, Yogo (Research Journal of Life Science, 2021)
Fruit flies (Diptera: Tephritidae) are important pests of horticultural crops. This study investigates the abundance and species richness of Bogor and Depok District as a center area horticulture commodity based on Cue Lure Trap. Each Cue Lure Trap was observed to record the abundance and species richness of fruit flies at seven days intervals from June until August 2021 in Bogor District (Babakan, Mekarsari and Parigi Mekar) and Depok District (Bedahan and Pancoran Mas), West Java, Indonesia. A total of 1,025 individuals were collected and consist of nine species of fruit fly i.e., Bactrocera albistrigata, B. carambolae, B. neocognata, B. verbascifoliae, Dacus conopsoides, D. longicornis, Zeugodacus calumniata, Z. caudatus, and Z. cucurbitae. The number of individuals of fruit flies was highest in the Bedahan, Depok District (F = 5.454, P = 0.002). Zeugodacus cucurbitae was the most abundant species (792 individuals), representing 77.27% of the specimens collected during the sampling period. The highest Shannon–Wiener diversity index of all fruit flies captured in this study was in Bedahan, Depok (1.11) and the lowest in Parigi Mekar, Bogor (0.23). A Bray–Curtis analysis showed that the species compositions of fruit flies on Bedahan and Parigi Mekar had a similarity of 70.1%.